Pengaruh BI Rate, FED Rate, Utang Luar Negeri, dan Cadangan Devisa Terhadap Nilai Tukar Rupiah di Indonesia - Dera Laudy Sari; Hilmiatus Sahla (Ali Institute of Research and Publication, 2026)
The main objective of this study is to determine influence of the BI rate, the Fed Rate, foreign debt, and foreign exchange reserves on the rupiah exchange rate in Indonesia both the partially and simultaneously. This study uses a descriptive approach and secondary data, namely data from Bank Indonesia from 2015 to 2025, with a total of 44 data samples, with the entire data population consisting of X1, X2, X3, X4, and Y. Data analysis techniques used EViews 10 with classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficient of determination (R2) tests. The partial results show that the BI rate has no significant effect on the exchange rate with a value of 0.057 > 0.05. The Fed Rate has an effect on the rupiah exchange rate with a value of 0.031 < 0.05. Foreign debt has no significant effect on the rupiah exchange rate with a value of 0.1228 > 0.05. Foreign exchange reserves have a significant effect on the rupiah exchange rate, with a value of 0.0233 < 0.05. Meanwhile, the BI rate, the Fed Rate, foreign debt, and foreign exchange reserves simultaneously have a significant effect with a probability value of 0.000000, which is less than 0.05. The coefficient of determination test results, with a value of 0.5975, indicate that the independent variables explain 59.75% of the exchange rate variance, while other factors explain the remaining 41.25%. Keywords: BI Rate, FED Rate, Foreign Debt, Foreign Exchange Reserves, Rupiah Exchange Rate